Study of the Performance of a Thermoelectric Refrigeration Membrane Cold Chamber Distillation Component - Hu, Junhu; Wu, Shunli; Liu, Hao; Yang, Xiaohong (Frontiers in Energy Research, 2022)
Solar-driven Membrane distillation (MD) is an emerging membrane-based evaporation technology with excellent prospects for separation industries. However, excellent membrane component properties have still limited the development of the MD system. In this paper, a cold chamber component of a Thermoelectric Refrigeration Membrane Distillation (TRMD) is manufactured. Then an experimental refrigeration performance of the component is studied to examine the coupling between the thermoelectric refrigeration and the membrane distillation process. Moreover, the effects of the membrane components properties are studied by changing the water flow rate, and the input current of thermoelectric refrigeration. The results showed that when the TRMD cold room inlet current is maintained stable and the heat dissipation intensity increases, the cooling temperature gradually decreases. Also, the temperature on the cold side tends to stabilize while the flow rate exceeds 600 L/h. In addition, the input power decreases as the heat dissipation intensity increases in the cooling dissipation intensity of the TRMD cold chamber is kept stable. And, the input power will reach a critical value while the water volume flow rate is over 500 L/h. Furthermore, the cooling rate reaches the maximum of 1.59 at the water volume flow rate of 700 L/h while the operating current of the Thermoelectric Refrigeration Membrane Distillation Component (TRMDC) is 12 A. It is concluded that the thermoelectric refrigeration component can supply great refrigeration power and a high Coefficient of Performance (COP) under small current conditions for the analysis of the thermoelectric performance of the TRMD cold chamber.